A novel frameshift variant in the TSPAN12 gene causes autosomal dominant FEVR. Issue 6 (13th April 2022) - Peng, Li; Dai, Erkuan; Xiao, Haodong; Zhao, Rulian; He, Yunqi; Li, Shujin; Yang, Mu; Yang, Zhenglin; Zhao, Peiquan
Abstract: Background: Familial exudative vitreoretinopathy (FEVR) is an inherited blinding eye disease with abnormal retinal vascular development. We aim to broaden the variant spectrum of FEVR and provide a basis for molecular diagnosis and genetic consultation. Methods: We recruited five FEVR patients from one large Chinese family. Whole‐exome sequencing (WES) and Sanger sequencing were applied to sequence, analyze, and verify variants on genomic DNA samples. Immunocytochemistry, western blot, qPCR, and luciferase assay were performed to test the influence of the variant on the protein expression and activity of the Norrin/β‐catenin pathway. Results: We identified a novel heterozygous frameshift variant c.533dupC (p.D179Rfs*6) in Tetraspanin 12 ( TSPAN12 ) gene that is related to FEVR. This variant caused degradation of the entire TSPAN12 protein, which failed to activate Norrin/β‐catenin signaling, possibly causing FEVR. Conclusion: Our study revealed a novel frameshift variant D179Rfs*6 in TSPAN12 that is inherited in an autosomal dominant manner. We found that D179Rfs*6 caused a failure to activate Norrin/β‐catenin signaling. This finding broadens the variant spectrum of TSPAN12 and provides invaluable information for the molecular diagnosis of FEVR. Abstract : We identified a novel heterozygous frameshift variant c.533dupC (p. D179Rfs*6) in Tetraspanin 12 (TSPAN12) that is related to FEVR. This variant caused degradation of the entire TSPAN12 protein, which failed to activate Norrin/β‐catenin signaling, possibly causing FEVR.